TRADITIONAL KNOWLEDGE OF MEDICINAL PLANTS IN TRIBES OF TRIPURA IN NORTHEAST, INDIA - Maria, Debbarma; Pala, Nazir A.; Kumar, Munesh; Bussmann, Rainer W. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The present study was carried out in Mandwi area and its outskirts of Tripura district of tribal areas Autonomous district council to document the available ethno-medicinal plants and their traditional application among Mandwi tribes. Methodology: Field explorations were carried out during the months of March-June 2013. The ethno-medicinal survey was conducted particularly with Tripuri tribe in Mandai area, with the help of local medicine men, locally known as bhoidho (Tripuri). Data were collected through structure questionnaires and observations during the field visits. Results: In the present study the local population used a total of 51 plant species belonging to 32 families to cure a variety of diseases. Of the 51 plants, 21 were herbs, followed by trees (17) and shrubs (8). Climbers and ferns had reported 2 species for each one grass species was found. Fabaceae was the dominant family with the highest number of species (6) followed by Asteracae (4 species) and Lamiaceae (5 species). Seven other families had 2 species each and 22 families were represented by a single species. In case single diseases, the highest number of plants (7 species) was used for dysentery, followed by body pain (6 species), cough (6 species) and toothache (6 species). Conclusion: The present study concluded that, the Tripuri tribes of the study area possess rich knowledge on the medicinal plants and their utilization. Thus the present study focuses on the documentation of the traditional knowledge of these valuable plants, which could enhance the potential of these medicinal plants to other communities as well and by understanding the importance, other communities can also be helpful for conservation of these resources for further use.